Technology-Based Learning Management of Maharah Istima' at Language Unit of Raudhah Al-Lughah Al-Arabiyah - Jannah, Mawaddatul; Shidqul Wafa, M. Azka; Mu'awanah, Elyatul; Mahmudah, Umi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Raudhah Al-Lughah Al-Arabiyyah is a language unit owned by Annuqayah Boarding School Sumenep Madura Boarding School. This language unit focuses on Arabic language learning which is non-formal. Istima's learning becomes one of the activities taught to students to help them understand Arabic utterances. Learning management is needed in Istima's learning activities to achieve effective learning goals. Effective learning objectives. The problem in this study is formulation: (1) how is the management of istima's learning which includes planning, implementation, and evaluation in The Raudhah Al-Lughah Al-Arabiyyah language unit. (2) what forms of technology are used as media in learning maharah istima'. This type of research is qualitative research; the sources are the chairman and some Raudhah Al-Lughah Al-Arabiyyah language unit members. Data collection using semi-structured interview techniques, and documentation. The final stages of data analysis are data reduction, data presentation, and conclusion in checking the validity of the data using triangulation. Results The results showed that: Istima's learning planning was prepared in the form of learning tools, including curriculum, media, materials, methods, determination of class, learning time, and place. Implementation of the system's learning activities went well; the steps included opening (introduction), delivery of material, and learning activities. Evaluation is carried out by the language unit Raudhah Al-Lughah Al-Arabiyyah with formative (day) and summative (every semester).